Perspectives on issues, challenges, and preferred futures for maternal, newborn, and child health in Arusha and Ngorongoro, Tanzania. Issue 2 (15th March 2018) - Dietrich Leurer, Marie; Petrucka, Pammla
Abstract: To articulate community perspectives on maternal, newborn, and child health issues, challenges, and preferred visions, the Mama Kwanza Socioeconomic Health Initiative (MKSHI), a Canadian–Tanzanian partnership, undertook a multimethod needs assessment using a community development approach. This paper reports on dialog with a cross-section of 12 health care providers and 15 stakeholders. The findings provided rich narratives on the health care context in the MKSHI Arusha and Ngorongoro service areas. Barriers to quality health care included complex socioeconomic needs, poor accessibility, providers requiring continuing education, inadequately staffed and resourced clinics, lack of service integration, and poor quality work life for providers. Ongoing community participation in MKSHI planning is required to attain preferred visions of equitable and accessible health services, knowledgeable and caring providers, and well-resourced programs. The assessment highlighted the importance of international development projects facilitating community consciousness-raising and dialog to create community partnerships that will enhance project effectiveness and sustainability.